Design and technological provision of wear resistance of elastomer surface of rubber-cord casings of damping devices - V. G. Churankin; A. V. Lyamtsev; V. V. Derkach (Омский научный вестник)
Two main factors are considered that determining the friction between non-lubricated surfaces of an elastomer and a solid base during their relative motion. The first one is adhesion in the areas of real (actual) catalysis and the second factor is the deformation component, which is due to the delay of recovery of the elastomer after the irregularity is introduced and it is called the hysteresis component of friction. One of the main problems of increasing the resource of pneumatic dampers is minimizing the wear of the covering layer of the rubber-cord casing (RCC). The wear of the RCC is due to the fact that sliding friction occurs in the process of contact between the metal surface and the surface of the RCC, as a result of which the cover layer of the RCC (in some cases with the first cord layer) wears out, depending on the chemical composition of the rubber and the features of the operation of the pneumatic shock absorber. In order to minimize the wear of rubber, it is proposed to change the design of the pneumatic damper so that rolling friction dominates in the contact between the surfaces of rubber and metal.